2014
DOI: 10.1007/s11274-014-1792-z
|View full text |Cite
|
Sign up to set email alerts
|

Spirotetronate antibiotics with anti-Clostridium activity from Actinomadura sp. 2EPS

Abstract: The rare actinomycetes strain 2EPS was isolated from soil and analysis of cultural, morphological characteristics, diaminopimelic acid content of its cell wall, and 16S rRNA gene sequence indicates that 2EPS belongs to genus Actinomadura. In addition, neighbor-joining phylogenetic tree also confirmed the relationships of this strain to other members of Actinomadura. A butanol extract with antibacterial activity was purified by reversed-phase chromatography to obtain three bioactive compounds, designated as com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…In addition to the antibacterial activity of spirotetronate 2EPS-A-C (Euanorasetr et al, 2015), 2EPS-B also showed antiviral activity against DENV-2. The anti-dengue screening assay relies on both the inhibitory ability of the tested compound against the recombinant NS2B-NS3 protease of DENV-2, as well as the effect on viral infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the antibacterial activity of spirotetronate 2EPS-A-C (Euanorasetr et al, 2015), 2EPS-B also showed antiviral activity against DENV-2. The anti-dengue screening assay relies on both the inhibitory ability of the tested compound against the recombinant NS2B-NS3 protease of DENV-2, as well as the effect on viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…2EPS-A-C was purified from Actinomadura sp. 2EPS based on the previous report (Euanorasetr et al, 2015). Purified compounds were dissolved in dimethylsulfoxide (DMSO) to obtain a final concentration of 20 mg/ml as a stock solution.…”
Section: Spirotetronate Compounds Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…[21,22] Three similar spirotetronate antibiotics decatromicins 9-11 were obtained from Actinomadura sp. 2EPS in 2015 [23] with potent activity against Clostridium, similar to compound 8, these compounds contain di (tri)-chloropyrrole side chains attached to the aminodeoxy sugar-spirotetronate through amide linkages. Compounds 9 and 11 displayed amazing antibacterial activity against Clostridium perfringens S107 with MIC values of 0.63 μg/mL; moreover, they also showed strong activity against Clostridium difficile 630 with MIC value of 0.08 μg/mL.…”
Section: Marine-based Polyketides With Diverse Bioactivitiesmentioning
confidence: 99%
“…However, some species have been isolated from patients, such as Actinomadura sputi (Yassin et al, 2010). This genus is of great importance in several domains, including the production of new bioactive metabolites active against pathogenic microorganisms (Euanorasetr et al, 2015). Species of the genus Actinomadura produce an extensively branched non-fragmenting substrate mycelium and, generally, aerial mycelium is moderately developed or absent.…”
mentioning
confidence: 99%